LEGITIMASI SANIRI NEGERI: STUDI ANTROPOLOGI BUDAYA ATAS RESISTENSI TERHADAP SISTEM MARGA KUASA DI NEGERI SEITH - M. Ridwan Tunny Dewiyanti Tomia (DIALEKTIKA, 2018)
Study sought to answer two research questions: (1) how Saniri domestic legitimacy in the role of indigenous peoples in the framework of State Seith, and (2) how social resistance against the power of the clan as a socio-cultural changes in society Seith State. The study used a phenomenological approach to the collection of data through observation and interviews with informants consisting of religious leaders, traditional leaders, soa head and head of youth. The results showed that the role of indigenous perangkar device- has spawned a local wisdom that comes from the rules, values and norms of the local community. The other side, which became the social dynamics in society Seith State is, as a result of political messages received by members of the community through print and electronic media has given rise to excessive openness and democracy